INFESTASI CAPLAK (Boophilus microplus) PADA TERNAK SAPI DI DESA PINABETENGAN KECAMATAN TOMPASO KABUPATEN MINAHASA - Konore, Jordan Ch.; Lomboan, Agustinus; Pudjihastuti, Endang; Sane, Srimalasinha; Nangoy, Meis (ZOOTEC, 2019)
This research was conducted in Pinabetengan village to calculate the prevalence and preference of tick infestations in cattle in Pinabetengan Village, Tompaso District, Minahasa Regency. This study uses the Purposive Random Sampling method. 64 cattles were used as samples. Collecting ticks starts from the head, neck, back, groin, legs, and tail, then put in a bottle containing 70% alcohol based on the body parts of the animal. Based on the result researchÂ Â  that 30 cattles were found to be infested of tick. Preferences of ticks on body parts of cattle show that at the groin is the most infestation of ticks. The tick infestation preference based on sex it turn out that female cattle are more often infested with tick. Based on the results and discussion it can be concluded that the cattle in the North Pinabetengan village infested with Boophilus microplus tick is 46.9%. Preference for tick infestation on the body parts that are most commonly found in the groin of cattle. Preference for tick infestation in female cattle is 4.38 ticks, while male cattle are 3.33 ticks.Keywords: Ticks, Infestations, Preference, Prevalence, Cow